2020
DOI: 10.1038/s41598-020-59811-9
|View full text |Cite
|
Sign up to set email alerts
|

Age of puberty and Sleep duration: Observational and Mendelian randomization study

Abstract: Earlier age of puberty has detrimental consequences for many aspects of health. Here, for the first time, we assessed the association of earlier puberty with sleep duration observationally and with validation using Mendelian Randomization. In the "Children of 1997" birth cohort (n = 8,327), we used adjusted multivariable logistic regression to assess the associations of each clinically assessed marker of earlier puberty with self-report sleep duration in adolescence. Using two-sample MR, we assessed the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…The relationship between physical activity and puberty timing remained controversial, since most studies were conducted in elite athletes, and little evidence was seen from general population samples (12) . Later age of menarche seemed to be associated with longer sleep duration (13) , but sleep duration had a limited connection with the age of sexual development in another study (14) . The onset of puberty occurred significantly earlier among people with smoking (15) , without drinking alcohol before puberty (16) .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The relationship between physical activity and puberty timing remained controversial, since most studies were conducted in elite athletes, and little evidence was seen from general population samples (12) . Later age of menarche seemed to be associated with longer sleep duration (13) , but sleep duration had a limited connection with the age of sexual development in another study (14) . The onset of puberty occurred significantly earlier among people with smoking (15) , without drinking alcohol before puberty (16) .…”
Section: Introductionmentioning
confidence: 87%
“…Later age of menarche seemed to be associated with longer sleep duration (13) , but sleep duration had a limited connection with the age of sexual development in another study (14) . The onset of puberty occurred significantly earlier among people with smoking (15) , without drinking alcohol before puberty (16) .…”
mentioning
confidence: 87%
“…Pubertal youth experience delayed sleep phase (the natural tendency for later bedtime), longer sleep latency, less deep sleep, and a greater tolerance to stay up compared to pre-pubertal youth [ 132 ]. In a Chinese cohort study, older age at menarche was associated with longer sleep duration (OR = 1.11; 95% CI = 1.01–1.21), though other measures of puberty timing (breast, genitalia, and pubic hair development) were unrelated to sleep duration [ 133 ]. Another study found that pubertal maturation (measured by Tanner stages 1 to 5) was associated with a progressive increase in the prevalence of insomnia symptoms, which more significantly affects girls: 3.4–12.2% in girls (3.6-fold) compared to 4.3–9.1% in boys (2.1-fold) [ 134 ].…”
Section: Methodsmentioning
confidence: 99%
“…(4) Furthermore, confounding bias might constitute the main source of the inconsistencies across studies. Multiple factors, such as social and economic factors, physical activity, sleep, and dietary habit, might obscure the relationship between obesity and puberty timing (36)(37)(38)(39). To overcome the problem of confounding bias, the propensity score-based inverse probability weighting (IPW) approach has been proposed recently (40).…”
Section: Introductionmentioning
confidence: 99%